42nd AIAA Plasmadynamics and Lasers Conference 2011
DOI: 10.2514/6.2011-3280
|View full text |Cite
|
Sign up to set email alerts
|

Flight Measurements of Aero-Optical Distortions from a Flat-Windowed Turret on the Airborne Aero-Optics Laboratory (AAOL)

Abstract: The optical environment of a flat-window hemisphere-on-cylinder turret during flight tests in Notre Dame's Airborne Aero-Optics Laboratory was evaluated. Aero-optical aberrations around the turret were measured using a high-speed (up to 20 kHz) Shack-Hartmann wavefront sensor providing the most complete aero-optical mapping to date. The primary data was acquired at Mach 0.5 at an altitude of 15,000 ft, with a subset of the data collected at Mach 0.4 for verification of scaling relationships. During each flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Porter et al 8 showed that, for a three dimensional (3-D) turret, the same phenomenon depended on both elevation and azimuth, even for the same LOS. However, Porter's analysis also suggested that the fluid dynamics should not be terribly sensitive at these particular combinations of azimuth and elevation, which are viewing fully separated flow, but in the region where higher-order OPD is declining due to aperture effects.…”
Section: Aaol Structure Functionsmentioning
confidence: 99%
“…Porter et al 8 showed that, for a three dimensional (3-D) turret, the same phenomenon depended on both elevation and azimuth, even for the same LOS. However, Porter's analysis also suggested that the fluid dynamics should not be terribly sensitive at these particular combinations of azimuth and elevation, which are viewing fully separated flow, but in the region where higher-order OPD is declining due to aperture effects.…”
Section: Aaol Structure Functionsmentioning
confidence: 99%
“…18 The original aero-optical wavefronts were produced by turbulence over a flat-windowed turret 18,[27][28][29] during a flight test in which a continuous-wave laser was transmitted between two planes flying in a constant formation at an altitude of 4570 m. The planes were separated by approximately 50 m to ensure aero-optical turbulence was the primary source of wavefront aberrations. Other significant parameters for the flight test are give in Table 1.…”
Section: Aero-optical Wavefront Disturbances In the Ao Experimentsmentioning
confidence: 99%
“…A detailed analysis of the statistics of the AAOL data has been published. 18 Since the control loops in this paper attempt to minimize the total phase error that would be encountered in similar airborne environments, no attempts were made to distinguish between the sources of the measured turbulence.…”
Section: Aero-optical Wavefront Disturbances In the Ao Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chapter 2, the simulation model and theory for digital holography recording and reconstruction is presented. Chapter 3 discusses the aero-optical wavefront data [2,3] used in this dissertation, while Chapter 4 explains the image sharpness algorithm and the model representation of the atmospheric wavefronts.…”
Section: Introductionmentioning
confidence: 99%